2002
DOI: 10.1051/animres:2002016
|View full text |Cite
|
Sign up to set email alerts
|

Feeding behaviour and intake of heifers fed on hays of various quality, offered alone or in a choice situation

Abstract: -We studied the feeding behaviour of cattle offered unconstrained choices between two hays of either different or similar nutritive values, and linked these choices to their behaviour when the same forages were offered alone. Over successive 10-day periods, six 15-month-old Aubrac heifers received three hays (a leafy one, G, and two late cut ones, C1 and C2, of very similar nutritive value), ad libitum, alternately alone and associated two by two. As expected, the heifers ate more G than C1 or C2 when the hay … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
2

Year Published

2005
2005
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 24 publications
1
19
0
2
Order By: Relevance
“…This was true for sheep preferring the flavour presented first within a conditioning period over that presented second (Arsenos et al, 2000), for ewes preferring the opposite species (i.e. white clover or ryegrass) to the one they had previously grazed (Newman et al, 1992;Parsons et al, 1994), and for heifers temporarily increasing their preference for the hay that had not been offered during the previous period (Ginane et al, 2002). The authors suggested that the preference for the 'new' hay could be explained by (i) the animal's need to select a balanced diet that best meets its homeostatic requirements or (ii) the animals' search for rarity for functional purposes, such as maintaining gut flora diversity or (iii) an attractive effect of novelty, considered as a search for diversity.…”
Section: Sensory Characteristics: a Way To Get Pleasurementioning
confidence: 95%
“…This was true for sheep preferring the flavour presented first within a conditioning period over that presented second (Arsenos et al, 2000), for ewes preferring the opposite species (i.e. white clover or ryegrass) to the one they had previously grazed (Newman et al, 1992;Parsons et al, 1994), and for heifers temporarily increasing their preference for the hay that had not been offered during the previous period (Ginane et al, 2002). The authors suggested that the preference for the 'new' hay could be explained by (i) the animal's need to select a balanced diet that best meets its homeostatic requirements or (ii) the animals' search for rarity for functional purposes, such as maintaining gut flora diversity or (iii) an attractive effect of novelty, considered as a search for diversity.…”
Section: Sensory Characteristics: a Way To Get Pleasurementioning
confidence: 95%
“…Provenza et al (1996) described that lambs enhanced their intake when several feeds were offered simultaneously as compared to offering only one feed, no matter whether the feeds on offer had similar or different quality, or differed in flavour. Ginane et al (2002) reported a higher daily DM intake when a choice among two hays of different or similar quality was offered than when one of these hay types was offered alone and explained this by an increased motivation to eat when a diverse offer is available. Even though high quality feeds are preferred by the animals in a choice situation, feeds with lower quality might help to motivate intake simply by increasing the diversity on offer (Ginane et al, 2002), because monotonous diets might lead earlier to a sensory-specific satiety (Rolls, 1986) thus decreasing the motivation to eat due to the lack of feed alternatives (Villalba et al, 2010).…”
Section: Choice Vs No-choice Situations With Low-quality Foragesmentioning
confidence: 99%
“…Ginane et al (2002) reported a higher daily DM intake when a choice among two hays of different or similar quality was offered than when one of these hay types was offered alone and explained this by an increased motivation to eat when a diverse offer is available. Even though high quality feeds are preferred by the animals in a choice situation, feeds with lower quality might help to motivate intake simply by increasing the diversity on offer (Ginane et al, 2002), because monotonous diets might lead earlier to a sensory-specific satiety (Rolls, 1986) thus decreasing the motivation to eat due to the lack of feed alternatives (Villalba et al, 2010). When testing different Mediterranean woody forages offered for 6 h/d by varying the number of feeds on offer between each 5-day period, intake increased or decreased along with the number of feeds (Rogosic et al, 2006(Rogosic et al, , 2007 which was explained by the changing biochemical diversity.…”
Section: Choice Vs No-choice Situations With Low-quality Foragesmentioning
confidence: 99%
See 2 more Smart Citations